Terapi Aktivitas Kelompok Tebak Benda sebagai Upaya Stimulasi Kognitif pada Lansia di PSTW Budi Mulia 2 Jakarta Barat - Adawiyah, Siti Robeatul; Prastiwi, Nurmalyta Dwi; Nurrahmawati; Kamillah, Aulia Hayatul; Rahmadani, Awaliyah; Oktaviani, Bella Eka; Cahyaseno, Dwi Putri; Ervina; Mutmaisah, Iis; Adiyansyah, Indra; Masfufah, Dian Siti (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: The elderly are an age group vulnerable to cognitive decline, such as forgetfulness, difficulty concentrating, and decreased thinking ability. One non-pharmacological intervention that can be applied to stimulate memory is Group Activity Therapy (GAT) using an object guessing game. Objective: To improve the elderly's knowledge and stimulate cognitive function through enjoyable and educational group activities. Method: This activity was conducted on April 25, 2025, at Wisma Pisang, Budi Mulia 2 Social Welfare Institution for the Elderly in West Jakarta. Fifteen male elderly residents participated. Their knowledge was assessed using a pre-test and post-test. Result: Before the activity, 73.3% of participants had low knowledge. After the therapy and education session, 60% showed an increase in knowledge to the good category. Conclusion: The object guessing group therapy is effective in increasing elderly knowledge about the therapy itself while providing cognitive and social stimulation in a positive atmosphere.